Rancang Toko Online SanavaCoffee via Lynk.ID dalam Peningkatan Penjualan Produk Kopi - Abdul Majid, Basrul; Bengi, Eva Simah; Sayuti, Ahmad; Sihite, Nadya Afyuni (J-SIGN (Journal of Informatics, Information System, and Artificial Intelligence), 2025)
SanavaCoffee is a small and medium-sized enterprise (SME) in the coffee sector, offering a wide range of products such as ground coffee, coffee beans, coffee bracelets, coffee masks, and tea bags. In light of the increasing prevalence of e-commerce in Indonesia, SanavaCoffee has embraced digital technology by utilizing the Lynk.id platform to create a modern e-commerce website. This study focuses on designing a website that is not only effective and interactive but also user-friendly for customers, taking full advantage of the features provided by the Lynk.id platform. The methodology employed in this research includes a thorough analysis of requirements, the design of the user interface, implementation of key features, and comprehensive system testing. The results reveal that the new website has improved operational efficiency by 35% and broadened marketing reach by 60%. Thus, the integration of the Lynk.id platform serves as a pivotal strategy for advancing the digital transformation of SMEs in the coffee industry. Additionally, this study offers practical insights and technical guidance for other SMEs looking to adopt e-commerce technologies, contributing to the ongoing dialogue about digital innovation in small businesses.